METODE KRITIK HADIS PERSPEKTIF MUHAMMAD SYUHUDI ISMAIL - Dadah Dadah; Cecep Rahmat (IAIN Syekh Nurjati Cirebon, 2022)
In Indonesia, Muhammad Syuhudi Ismail is known as a preacher, communityleader, and Islamic scientist who has very strong intellectual roots, masters variousfields of Islamic knowledge and has high dedication to the development of hadithscience in Indonesia. His thoughts related to the development of hadith studiesare widely articulated through a number of books, articles and papers whichhe wrote through local and national media. He has produced no less than 164scientific papers, both in the form of scientific treatises, books, research results,notes/notes, papers, texts of speeches, articles, theses and dissertations. The workshe produces are not only limited to the field of hadith, but also include the fieldsof fiqh, astronomy, thought, and other fields of science. In addition, three volumesof works and thirteen information contributions for the Islamic Encyclopedia.Among Syuhudi's works, around eight have become the main books in the subjectof hadith and hadith science in all Faculties of Religion in Indonesia, especially theDepartment of Hadith Science or Hadith Interpretation, for example Introductionto Hadith Science (1987) and Ulumul Hadith (1992).